Professio-graphic approach to psychological preparation of future specialists of agrarian sphere to professional activity - POLOZENKO, Oksana (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2013)
In the article it was grounded the purposefulness of application of the professional-graphic approach to the psychological preparation of future specialistsof agrarian field, the peculiarities of the professional activity of the agrarianswere studied, it was analyzed the notion „professio-graphic approach”, „professiography”,„professiogramm